PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK BADAN - Andreanto, Yohanes; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The demand for the enhancement of revenue, awareness and taxpayer compliance and some improvements and the fundamental changes in all aspects of taxation has become the reason for tax reform. The reformation of tax administration which has been carried out by Directorate General of Taxation as the manifestation of the enhancement of service quality of taxation to the taxpayer one of them is the development of the tax payable report by using modern taxation administration. The manual taxation administration system is considered to have some weaknesses particularly for corporate taxpayer who conducts many transactions has to enclose documents (hardcopy) in quite large amount to the KPP. This research uses quantitative method which is carried out by conducting survey, the population is all corporate taxpayers in the environment of Kantor Pelayanan Pajak Pratama Surabaya Sawahan with anincorporated status PT (Perseroan Terbatas). The data is the primary data which has been done by issuing questionnaires to the corporate taxpayers which match with criteria to be selected as respondents. Overall, the result of the research i,e. Organization structure, organization strategy, organization procedure, and organization institution which are included in indicators of modern taxation administration at KPP Pratama Surabaya Sawahan has positive influence to the rate of compliance of corporate taxpayers.Keywords: Modern tax administration, compliance of taxable employer, corporate taxpayers.